2020
DOI: 10.1038/s41467-019-14067-4
|View full text |Cite
|
Sign up to set email alerts
|

Bright ligand-activatable fluorescent protein for high-quality multicolor live-cell super-resolution microscopy

Abstract: We introduce UnaG as a green-to-dark photoswitching fluorescent protein capable of highquality super-resolution imaging with photon numbers equivalent to the brightest photoswitchable red protein. UnaG only fluoresces upon binding of a fluorogenic metabolite, bilirubin, enabling UV-free reversible photoswitching with easily controllable kinetics and low background under Epi illumination. The on-and off-switching rates are controlled by the concentration of the ligand and the excitation light intensity, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 69 publications
3
43
0
Order By: Relevance
“…This set of experiments suggested that the observed reversible photobleaching was likely due to photoisomerization and/or photoejection of the chromophore, as previously proposed to explain the reversible photobleaching observed when labeling FAST and its variants with low concentrations of HBR derivatives 28,23 . This singular photochemical signature might be used advantageously for selective imaging techniques based on kinetic discrimination 29,30 or for single-molecule localization microscopies 31,32 .…”
Section: Resultsmentioning
confidence: 99%
“…This set of experiments suggested that the observed reversible photobleaching was likely due to photoisomerization and/or photoejection of the chromophore, as previously proposed to explain the reversible photobleaching observed when labeling FAST and its variants with low concentrations of HBR derivatives 28,23 . This singular photochemical signature might be used advantageously for selective imaging techniques based on kinetic discrimination 29,30 or for single-molecule localization microscopies 31,32 .…”
Section: Resultsmentioning
confidence: 99%
“…These limitations and the difficulty associated with in-vivo study of biological specimens is a handicap for this promising technique. On the bright side, it should be possible to design super bright non-toxic photoactivable probes that can be easily conjugated with the protein-of-interest for studying biological processes [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…These limitations and the di culty associated with in-vivo study of biological specimens is a handicap for this promising technique. On the bright side, it should be possible to design super bright non-toxic photoactivable probes that can be easily conjugated with the protein-of-interest for studying biological processes [37] [38].…”
Section: Discussionmentioning
confidence: 99%